2015
DOI: 10.1016/j.cej.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerium doped copper/ZSM-5 catalysts used for the selective catalytic reduction of nitrogen oxide with ammonia

Abstract: Abstract:The CuCe/ZSM-5 catalysts with different cerium loadings (0, 0.5, 1.0, 1.5 and 2.0 wt.%) was investigated to evaluate the correlation between structural characteristics and catalytic performance for the selective catalytic reduction (SCR) of NO by NH3. It was found that the addition of cerium increased copper dispersion and prevented its crystallization. According to the results of X-ray photoelectron spectroscopy (XPS) and temperature-programmed reduction by hydrogen (H2-TPR), copper species were enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…The Cu2p3/2 peaks can be deconvoluted to two peaks, and the peaks at 933.4 eV represent the agglomerated CuO nanoparticles on the surface of catalysts, and the one at BE ¼ 935.2 eV is attributed to isolated Cu 2+ ion coordinated to supercial oxygen atoms of zeolite. 18,20 Since the diffraction peaks of CuO species could not be observed in the XRD spectra, these CuO crystallites' size should be lower than 3 nm. " was calculated by Cu (at%) Â (m/(1 + m)) and "CuO" was calculated by Cu (at%)/(1 + m).…”
Section: Catalytic Activity Testingmentioning
confidence: 99%
“…The Cu2p3/2 peaks can be deconvoluted to two peaks, and the peaks at 933.4 eV represent the agglomerated CuO nanoparticles on the surface of catalysts, and the one at BE ¼ 935.2 eV is attributed to isolated Cu 2+ ion coordinated to supercial oxygen atoms of zeolite. 18,20 Since the diffraction peaks of CuO species could not be observed in the XRD spectra, these CuO crystallites' size should be lower than 3 nm. " was calculated by Cu (at%) Â (m/(1 + m)) and "CuO" was calculated by Cu (at%)/(1 + m).…”
Section: Catalytic Activity Testingmentioning
confidence: 99%
“…270 and 450 °C. The lower temperature desorption is attributed to adsorption at weak acid sites (Brønsted and Lewis) with the high temperature desorption unequivocally assigned to NH 3 chemisorbed at strongly acidic Brønsted sites . All zeolites showed decreased NH 3 capacity following Cu impregnation, averaging a loss of 26.0 % (±5.4 %) of total strong‐Brønsted sites.…”
Section: Resultsmentioning
confidence: 92%
“…As H 2 -TPR studies suggested the presence of exchanged Cu 2 + species, the occupation of exchange sites was confirmed through desorption is attributed to adsorption at weak acid sites (Brønsted andL ewis)w ith the high temperature desorption unequivocally assigned to NH 3 chemisorbed ats trongly acidic Brønsted sites. [48][49][50][51][52][53] All zeolites showedd ecreased NH 3 capacity following Cu impregnation, averaging al oss of 26.0 %( AE 5.4 %) of total strong-Brønsted sites. This was supported by DRIFTS spectra in Figure 3ii which showed decreased intensity of the peak at 3607 cm À1 (OH groups coordinated to Td framework Al 3 + )f or each ZSM-5 following Cu impregnation.…”
Section: Zsm-5c Atalysed Alkane Oxidation Reactionsmentioning
confidence: 99%
“…Today, researchers tend to focus on different compound oxides for catalyst support since they possess great features that would result in the higher removal of nitric oxide. Zeolite Socony Mobil–5 (ZSM-5) [62], TiO 2 [37,47,5859], and Al 2 O 3 [60] are some of the examples of the most frequently used catalyst supports. The ZSM-5 support is reported to have a remarkable ion-exchange capacity [121].…”
Section: Reviewmentioning
confidence: 99%